2019
DOI: 10.1021/acs.jpcc.9b07207
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Dense Array of ZnO Nanowires Spatially Grown on ZnO/TiO2 Nanofibers and Their Ultraviolet Activated Gas Sensing Properties

Abstract: A three-dimensional heterostructure using selective growth of ZnO nanowires on TiO 2 /ZnO nanocomposite nanofiber by a novel combination of a postseeding method in an electrospinning process and a hydrothermal technique is presented in this work. A hierarchical dense array of ZnO nanowires with a diameter of 70−120 nm and an aspect ratio of about 10 on TiO 2 /ZnO composite nanofibers (ZnO@TiO 2 /ZnO) was fabricated. XRD, UV−vis, FESEM, HRTEM, TEM, EDX, and XPS analyses were used for characterization of nanofib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It should be noted that the TU and ZU photocatalysts exhibit lower photocatalytic efficiency due to the higher recombination rate of the photogenerated electron-hole pair. Moreover, the photodegradation performance increased with the increasing content of ZnO, due to the formation of the effective heterojunction and the inhibition of electron-hole pair recombination [31]. However, when the ZnO content was exceeded in TZU70, there was a saturation value and the overall heterostructure was unstable, leading to a decrease in the effective charge transfer process in the heterostructure and a decrease in photocatalytic efficiency [29].…”
Section: Photocatalytic Degradation Of Methyl Orange Using Uv-visible Lightmentioning
confidence: 99%
“…It should be noted that the TU and ZU photocatalysts exhibit lower photocatalytic efficiency due to the higher recombination rate of the photogenerated electron-hole pair. Moreover, the photodegradation performance increased with the increasing content of ZnO, due to the formation of the effective heterojunction and the inhibition of electron-hole pair recombination [31]. However, when the ZnO content was exceeded in TZU70, there was a saturation value and the overall heterostructure was unstable, leading to a decrease in the effective charge transfer process in the heterostructure and a decrease in photocatalytic efficiency [29].…”
Section: Photocatalytic Degradation Of Methyl Orange Using Uv-visible Lightmentioning
confidence: 99%
“…With the addition of ZnO, the absorption rate improved significantly, especially when m­(ZnO):m­(SiO 2 ) = 3:2, the absorption rate was close to 100%. This is attributed to the porous and uniformly rough structure constructed by the two nanoparticles, which allows light to be “trapped” within the structure for multiple refractions and provides a larger specific surface area and active sites, causing more photoelectric effects and thus increasing UV light absorption. , At this point, the absorptivity of the coating decreases when the ZnO content continues to increase, which might be due to the self-agglomeration of ZnO, resulting in uneven dispersion or shedding of particles. As a result, the UV absorption efficiency of the coating is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies on light‐activated gas sensors have repeatedly reported relatively improved gas responses and faster recovery characteristics under light illumination. [ 7,8 ] Considering the high‐performance requirements for gas sensors in IoE applications, further modifications of the sensory materials, other than just relying on their bulk properties, should precede the full utilization of the given light energy. In response, there have been numerous efforts reported to date with various strategies for light‐activated gas sensors including i) heterojunction engineering, [ 9 ] ii) noble metal decoration, [ 10 ] iii) utilization of nonoxide materials (2D, inorganic perovskites), [ 11,12 ] iv) incorporation of plasmonic nanoparticles, [ 13 ] and v) development of effective nanostructures.…”
Section: Figurementioning
confidence: 99%